The management of innovation processes - Barraza Macías, Arturo (Avances en Supervisión Educativa, 2007)
In the present article part of the question how to manage the innovation processes? This question leads, in first instance, to position to us conceptually and to define the model from as we approached its answer. At a second moment, locating to us in the scholastic scope, it is recognized that a democratic management and a director of scholastic center jeopardize with the same one, are indispensable conditions successfully to carry out the management of the educative innovation.